Dhikr and Prayer Guidance on Peace of Mind and Blood Pressure Control - Samsualam; Masriadi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The Effectiveness of Dhikr and Prayer Guidance on Peace of Mind and Blood Pressure Control. WHO data (2015) indicate the 1.13 billion people worldwide with hypertension. The purpose of this study is to know the effectiveness of dhikr and prayer guidance on peace of mind and blood pressure control in the elderly with hypertension. Methods: The research design was a quasi-experiment with a pretest-posttest approach. The samples are 24 respondents. Results: The results showed that the pvalue0.036 <0.05 means no significant effect on the peace of mind of the elderly with hypertension in the intervention group who given dhikr and prayer guidance. Pre and post blood pressure tests in the intervention group obtained pvalue0.000 <0.05, which means that there is an effect of the intervention group variable (systole) on blood pressure. Conclusion: Dhikr and prayer instructions can be a complementary therapy in overcoming mental calm and blood pressure in the elderly with hypertension.We hope that the results of this study can be used as a reference material in providing therapy to patients with hypertension in order to help lower blood pressure.